Combining Electrospinning and Vapor-Phase Polymerization for the Production of Polyacrylonitrile/ Polypyrrole Core-Shell Nanofibers and Glucose Biosensor Application - Sapountzi, Eleni; Chateaux, Jean-François; Lagarde, Florence (Frontiers in Chemistry, 2020)
In this work, polyacrylonitrile (PAN) nanofiber mats coated with conductive polypyrrole layers were produced at the surface of gold electrodes by a two-step approach combining electrospinning and vapor phase polymerization. In the first step, smooth and uniform PAN fibers exhibiting an average diameter of 650 ± 10 nm were generated through electrospinning of 12 wt% PAN solutions. The electrospun PAN fibers were impregnated with iron(III)tosylate (FeTos), annealed at 70°C and used as a robust and stable template for the growth of a thin layer of conductive polymer by co-polymerizing pyrrole (Py) and pyrrole-3-carboyxylic acid (Py3COOH) vapors under nitrogen atmosphere. The carboxyl groups introduced in polypyrrole coatings enabled further covalent binding of a model enzyme, glucose oxidase. The effect of different parameters (concentration of FeTos into the immersion solution, time of polymerization, Py/Py3COOH molar ratio) on the PAN/PPy/PPy3COOH/GOx impedimetric biosensor response was investigated. In the best conditions tested (immersion of the PAN fibers into 20 wt% FeTos solution, polymerization time: 30 min, 1:2 Py/Py3COOH ratio), the biosensor response was linear in a wide range of glucose concentration (20 nM−2μM) and selective toward ascorbic and uric acids. A very low limit of detection (2 nM) compared to those already reported in the literature was achieved. This value enables the determination of glucose in human serum after a large dilution of the sample (normal concentrations: 3.6 mM−6.1 mM range).